1992
DOI: 10.1159/000236091
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Soluble lnterleukin-2 Receptors in Young Healthy Cigarette Smokers: Lack of Association with Atopy or Airways Hyperresponsiveness

Abstract: To study the relationship of atopy and nonspecific airways hyperresponsiveness to circulating levels of soluble interleukin-2 receptors (sIL-2R), we measured serum sIL-2R concentrations in 40 young, healthy smokers and non-smokers. Levels of sIL-2R were significantly higher in current smokers than in nonsmokers (median sIL-2R levels 605 vs. 398 U/ml, respectively; p < 0.05). Serum sIL-2R levels were not related to nonspecific airways hyperresponsiveness to methacholine, allergy skin test reactivity, doctor-dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Both nicotine and cotinine induce increased production of IL-Ix, IL-2, IL-3, IL-4, and 8 (4) IL-6 in vitro without an effect on IgE production or classswitching (Fischer and Konig, 1994). Increases in serum IL-2 receptor have been noted in smokers compared with non-smokers (Tollerud et al, 1992). Finally, levels of leukotriene B4 (LTB4) are higher in sera of non-allergic smokers than in that of non-smokers with or without allergies (Yanagisawa and Nagai, 1993).…”
Section: Effects Of Tobacco and Smoking On Levels Of The Cytokine Thamentioning
confidence: 96%
See 1 more Smart Citation
“…Both nicotine and cotinine induce increased production of IL-Ix, IL-2, IL-3, IL-4, and 8 (4) IL-6 in vitro without an effect on IgE production or classswitching (Fischer and Konig, 1994). Increases in serum IL-2 receptor have been noted in smokers compared with non-smokers (Tollerud et al, 1992). Finally, levels of leukotriene B4 (LTB4) are higher in sera of non-allergic smokers than in that of non-smokers with or without allergies (Yanagisawa and Nagai, 1993).…”
Section: Effects Of Tobacco and Smoking On Levels Of The Cytokine Thamentioning
confidence: 96%
“…The discordant data on T-cell proliferation and IL-2 production may be explained by data from other studies which indicate that the levels of soluble IL-2 receptor (sIL-2R) are higher in smoker than in non-smoker sera (Ginns et al, 1990;Tollerud et al, 1992Tollerud et al, , 1994Tollerud et al, , 1995. It is possible that sIL-2R sequesters IL-2 from the T-cells in smoker sera and hence limits both their proliferative capacity and their ability to provide help to B-cells.…”
Section: Effects Of Smoking and Tobacco On T-lymphocyte Cytokine Prodmentioning
confidence: 97%
“…In addition, the presence of markedly increased3, 9,8,23 or progressively increasing levels may be a poor prognostic sign.1218 Miscellaneous other conditions also can be as¬ sociated with higher than normal serum SIL2R. 24,25 The pathophysiologic importance of circulating SIL2R is not yet well defined. The SIL2R-modified alpha-chain homodimer6 structure is distinct from those of the cell surface high-or intermediate-affinity IL2R heterodimers.4'5 However, SIL2R does maintain low affinity interleukin-2 binding capacity.26 In the context of T-cell clonal expansion, SIL2R may be produced mainly by ma¬ lignant cells.…”
Section: Four Of Six Patients (Table Andmentioning
confidence: 99%
“…These differences in T-cells populations have also been reported in different studies in different countries. For example, the results obtained by Tollerud et al [41] have shown that CD4 + T-cells but not in CD8 + T-cells, CD3 + T-cells or CD19 + B-cells were higher in smokers compared to nonsmokers. Other T-cells subsets such as memory and naïve T-cells subpopulations were also increased in smokers [42].…”
Section: Discussionmentioning
confidence: 99%